The double burden of severe mental illness and cancer: a population-based study on colorectal cancer care pathways from screening to end-of-life care - A.-V. Seppänen; F. Daniel; S. Houzard; C. Le Bihan; M. Coldefy; C. Gandré (Cambridge University Press, 2024)
Abstract Aims Cancer is one of the main causes of death in persons with severe mental illness (SMI). Although their cancer incidence is similar, or sometimes even potentially lower compared to the general population, their cancer mortality remains higher. The role of healthcare provision and care equity in this mortality is increasingly being addressed in research, but available studies are limited in their scope. In this context, our aim was to compare colorectal cancer (CRC) care pathways from screening to end-of-life care in patients with and without pre-existing SMI on a national scale. Methods This research leverages real-world data from the French national health claims database, covering the entire population, to assess cancer screening, diagnosis, treatment and post-treatment follow-up as well as quality of care (QOC) pathways among patients with incident CRC in 2015-2018, considering whether they had pre-existing SMI. We matched patients with SMI with three patients without - on age, sex, region of residence, year of cancer incidence and cancer type and location at presentation - as well as nationally established quality of CRC care indicators and regression models adjusting for relevant socio-economic, clinical and care provider-related covariates. Results Among patients with incident CRC, 1,532 individuals with pre-existing SMI were matched with individuals without SMI. After adjusting for covariates, both colon and rectal cancer patients with SMI were less likely to participate in the national CRC screening programme and to receive advanced diagnostic examinations (e.g., colonoscopies and several complementary diagnostic examinations). They also had lower odds of receiving combined treatments (e.g., neoadjuvant chemotherapy, radiotherapy and excision) and of having access to targeted therapy or capecitabine but higher odds for invasive care (e.g., stoma). Colon cancer patients with SMI were also more likely to have no treatment at all, and rectal cancer patients with SMI were less likely to receive post-treatment follow-up. Suboptimal QOC was observed for both groups of patients, but to a higher extent for patients with SMI, with statistically significant differences for indicators focusing on diagnosis and post-treatment follow-up. Conclusions Our findings reveal discrepancies across the care continuum of CRC between individuals with and without SMI and provide initial avenues on where to focus future efforts to address them, notably at the entry and exit stages of cancer care pathways, while calling for further research on the mechanisms preventing equity of physical healthcare for individuals with SMI.